Long-term Sustainability Of Public Finance In The Central And Eastern EU Member States - Uryszek, Tomasz (Comparative Economic Research. Central and Eastern Europe, 2015)
The main goal of this article is to investigate the level of long-term sustainability of public finance in the Central and Eastern EU Member States. This aim is accompanied by the following hypothesis: an inability to generate primary surpluses and significantly growing public debt volumes prevent the attainment of sustainability in the area of public finance. The research method is based on GDP and public debt growth rates, as well as on the values of discounted primary fiscal balances at the actual and structural level. The research period covers the years 2000-2014. Data were taken from Eurostat, the European Commission's Directorate General for Economic and Financial Affairs and the European Central Bank.